Diseño de una planta pasteurizadora para obtener leche pasteurizada en la ciudad de San Pedro de Lloc - Huamán Moya, Félix Wilfredo (2006)
The present work has come true with the purpose to design a plant for dairy pasteurization at Pacasmayo's province. The project Trujillo with a capability considers the installation of the plant at city of 5 000 liters of milk per day. In the project he determines the profitability of the same and they give themselves the recommendations for his implementation